DIGITAL IMAGE PROCESSING MODELS AND ALGORITHMS FOR MEDICAL IMAGES - Rakhimov , Bakhtiyor; Otamuratov , Khurmatbek; O‘razmatov, Tokhir (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article explores modern approaches in the field of digital image processing, focusing on methods for noise detection and removal. It outlines the causes of noise in images and describes the main noise models - additive Gaussian noise and impulse noise. The advantages and applications of various filters, including linear and nonlinear, median, and rank filters, are discussed. The role of filtering in improving image quality is emphasized, particularly in fields such as medicine and digital communication systems.